Lactobacillus plantarum 5BG Survives During Refrigerated Storage Bio-Preserving Packaged Spanish-Style Table Olives (cv. Bella di Cerignola) - Lavermicocca, Paola; Angiolillo, Luisa; Lonigro, Stella L.; Valerio, Francesca; Bevilacqua, Antonio; Perricone, Marianne; Del Nobile, Matteo A.; Corbo, Maria R.; Conte, Amalia (Frontiers in Microbiology, 2018)
This paper proposes bio-preservation as a tool to assure quality and safety of Spanish-style table olives cv. Bella di Cerignola. Lactobacillus plantarum 5BG was inoculated in ready to sell olives packaged in an industrial plant by using a half-volume brine (4% NaCl; 2% sucrose). The samples were stored at 4°C. The survival of the inoculated strain, the microbiological quality, the sensory scores and the survival of a strain of Listeria monocytogenes inoculated in brines were evaluated. The persistence of the Lb. plantarum bio-preserving culture was confirmed on olives (≥6.5 Log CFU/g) and in brine (≥ 7 Log CFU/ml). Bio-preserved olives (SET1) showed a better sensory profile than chemically acidified control olives (SET2) and the texture was the real discriminative parameter among samples. Bio-preserved olives recorded better scores during storage because of their ability to retain good hardness, crunchiness and fibrousness without cracks. The inoculation of Lb. plantarum positively acted on the safety of olives, as the D-value of L. monocytogenes was reduced from 40 (SET2) to 5 days (SET1). In conclusion, Lb. plantarum 5BG and the physico-chemical conditions achieved in the settled procedure are suitable for the industrial packaging of Bella di Cerignola table olives, improving the process by halving brining volumes and avoiding chemical stabilizers, and significantly reducing the salt concentration. The final product is also safely preserved for almost 5 months as suggested by the reduction of the survival rate of L. monocytogenes.